Digital Uprisings and the Technocratic Turn: Assessing Nepal’s Trajectory as a Blueprint for Nigeria - Ndinojuo, Ben-Collins Emeka (Universitas Semarang, 2025)
Purpose: This article focuses on the transformation from democratic discontent to modern digital dissent as seen in the 2025 uprising led by youth in Nepal, culminating with the election of an interim Prime Minister on Discord as an early example of media activism, and beginning the process of transitioning toward a technocratic order from an actual change through mass protests. The investigation also covered the #ENDSARS protest in Nigeria in 2020 to understand why it failed to achieve the same success enjoyed by the Nepal protests despite both being orchestrated using digital media applications. Methods: A systems comparative case study design was employed to investigate the phenomenon of youth-driven digital disruption in Nepal and Nigeria. This research combines academic sources with proof from global news, policy papers, and studies of digital media about hashtag campaigns and memes on platforms like Discord, TikTok, and X. Findings: The findings attribute Nepal's success to a few things: anti-corruption issues coming together, smart Discord use for command, and an unstable political leadership. On the other hand, even with its digital strength, the #EndSARS movement in Nigeria suffered. Several factors explain the lack of stronger action, most importantly the absence of a clear plan after the protests and the disruption of the protests because of ethnic, sectarian, and religious divisions. Originality: This paper provides a novel comparative framework by juxtaposing Nepal’s successful 2025 ’digital coup’ against Nigeria’s arrested #EndSARS movement to isolate the specific political opportunity structures required for digital dissent to produce tangible change.